Resources and Methods for Named Entity Recognition in Serbia - Vitas, Duško; Pavlović-Lažetić, Gordana (Infotheca - Journal for Digital Humanities; Vol 9 No 1/2 (2008): Infotheca - Journal of Informatics and Librarianship, 2024)
In this paper we analyze the problem of named entity recognition in Serbian in view of its rich morphological system and syntactic constraints in the realization of this task. Special attention is given to the recognition of proper names. A method of lexical recognition based on an exhaustive morphological dictionary has been applied. Illustrative examples of the applied method are given.